Role of the Aryl Hydrocarbon Receptor in Controlling Maintenance and Functional Programs of RORγt+ Innate Lymphoid Cells and Intraepithelial Lymphocytes - Kiss, Elina A.; Diefenbach, Andreas (Frontiers in Immunology, 2012)
Mucosal RORγt-expressing innate lymphoid cells (ILC) play an important role in the defense against intestinal pathogens and in promoting epithelial homeostasis and adaptation thereby effectively protecting the vertebrate host against intestinal inflammatory disorders. The functional activity of RORγt+ ILC is under the control of environmental cues. However, the molecular sensors for such environmental signals are largely unknown. Recently, the aryl hydrocarbon receptor (AhR) has emerged as a master regulator for the postnatal maintenance of intestinal RORγt+ ILC and intraepithelial γδ T cells. AhR is a highly conserved transcription factor whose activity is regulated by environmental and dietary small molecule ligands. Here, we review the role of AhR signaling for the maintenance of intestinal immune cells and its impact on the immunological protection against intestinal infections and debilitating chronic inflammatory disorders.